Impact of Using Macromedia Flash-Based Audio-Visual Learning Media on Student Motivation to Learn About The Concept of Enthalpy Change - Nadhokhotani Herpi, Aini; Susilo, Ahmad; Saridewi, Nanda (Annpublisher, 2024)
Cultivating learning motivation is crucial for instilling passion in students for studying chemistry. However, traditional learning methods that rely on little media usage fail to enhance students' willingness to learn. Macromedia Flash learning media is a practical option for enhancing student learning motivation. This media promotes active student engagement and cultivates enthusiasm and passion for learning. This study aims to assess the impact of Macromedia Flash learning media on students' motivation to learn and their understanding of the subject of enthalpy change. The research methodology employed in this study is a quasi-experimental design with a posttest-only control group. The research was conducted at SMA Nusantara Plus, using class XI Science 1 as the experimental group and class XI Science 2 as the control group. Each group consisted of 33 students. The instrument used was a non-experimental tool in the form of a questionnaire consisting of 25 statements to assess learning motivation. The t-test conducted for the hypothesis test yielded a two-tailed Significance value of 0.000, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). The study's findings demonstrated that using Macromedia Flash learning media significantly impacted students' motivation to learn the material on enthalpy change.